Mangosteen xanthone γ-mangostin exerts lowering blood glucose effect with potentiating insulin sensitivity through the mediation of AMPK/PPARγ - Sih-Pei Chen (Elsevier, 2021)
Diabetes mellitus (DM) is concomitant with significant morbidity and mortality and its prevalence is accumulative in worldwide. The conventional antidiabetic agents are known to mitigate the symptoms of diabetes; however, they may also cause side and adverse effects. There is an imperative necessity to conduct preclinical and clinical trials for the discovery of alternative therapeutic agents that can overcome the drawbacks of current synthetic antidiabetic drugs. This study aimed to investigate the efficacy of lowering blood glucose and underlined mechanism of γ-mangostin, mangosteen (Garcinia mangostana) xanthones. The results showed γ-Mangostin had a antihyperglycemic ability in short (2 h)- and long-term (28 days) administrations to diet-induced diabetic mice. The long-term administration of γ-mangostin attenuated fasting blood glucose of diabetic mice and exhibited no hepatotoxicity and nephrotoxicity. Moreover, AMPK, PPARγ, α-amylase, and α-glucosidase were found to be the potential targets for simulating binds with γ-mangostin after molecular docking. To validate the docking results, the inhibitory potency of γ-mangostin againstα-amylase/α-glucosidase was higher than Acarbose via enzymatic assay. Interestingly, an allosteric relationship between γ-mangostin and insulin was also found in the glucose uptake of VSMC, FL83B, C2C12, and 3T3-L1 cells. Taken together, the results showed that γ-mangostin exerts anti-hyperglycemic activity through promoting glucose uptake and reducing saccharide digestion by inhibition of α-amylase/α-glucosidase with insulin sensitization, suggesting that γ-mangostin could be a new clue for drug discovery and development to treat diabetes.